2011
DOI: 10.1021/jf201702h
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Components Inhibit Amyloid Formation of Human Islet Amyloid Polypeptide in Vitro: Possible Link between Coffee Consumption and Diabetes Mellitus

Abstract: Global epidemic studies have suggested that coffee consumption is reversely correlated with the incidence of type 2 diabetes mellitus (T2DM), a metabolic disease. The misfolding of human islet amyloid polypeptide (hIAPP) is regarded as one of the causative factors of T2DM. Coffee extracts have three major active components: caffeine, caffeic acid (CA), and chlorogenic acid (CGA). In this study, the effects of these major coffee components, as well as dihydrocaffeic acid (DHCA) (a major metabolite of CGA and CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
99
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 48 publications
3
99
0
1
Order By: Relevance
“…Fluorescence measurement was conducted to monitor the extent of fibril formation of hIAPP [11][12][13][14][15][16][17][18][19][20] by LS55 Fluorescence Spectrofluorometer system (PerkinElmer Inc, UK). Time curves of thermophoresis for binding affinity were obtained on the microscale thermophoresis (MST) setup (Monolith NT.115 system, NanoTemper Technologies GmbH, Germany).…”
Section: Apparatusmentioning
confidence: 99%
See 4 more Smart Citations
“…Fluorescence measurement was conducted to monitor the extent of fibril formation of hIAPP [11][12][13][14][15][16][17][18][19][20] by LS55 Fluorescence Spectrofluorometer system (PerkinElmer Inc, UK). Time curves of thermophoresis for binding affinity were obtained on the microscale thermophoresis (MST) setup (Monolith NT.115 system, NanoTemper Technologies GmbH, Germany).…”
Section: Apparatusmentioning
confidence: 99%
“…As lipopeptides have some hydrophobic groups, which are similar to the reported aggregation inhibitors, and some lipopeptides could prevent cells from depositing of amyloid fibrils, several potential lipopeptide inhibitors have been engineered and synthesized, which have been assessed for their inhibitory effect in preventing amyloid fibrils formation of hIAPP [11][12][13][14][15][16][17][18][19][20] by using the conventional thioflavin-T fluorescence assay and new technique microscale thermophoresis (MST). The final amyloid fibrils of hIAPP [11][12][13][14][15][16][17][18][19][20] were characterized by transmission electron microscopy. Results suggested that with the increasing length of alkyl chain, the antiaggregation efficiency of lipopeptide inhibitors towards hIAPP 11-20 increased gradually.…”
mentioning
confidence: 99%
See 3 more Smart Citations